Bone marrow lesions, subchondral bone cysts and subchondral bone attrition are associated with histological synovitis in patients with end-stage knee osteoarthritis: a cross-sectional study. Issue 11 (November 2015) - Yusup, A.; Kaneko, H.; Liu, L.; Ning, L.; Sadatsuki, R.; Hada, S.; Kamagata, K.; Kinoshita, M.; Futami, I.; Shimura, Y.; Tsuchiya, M.; Saita, Y.; et al.
Summary: Objective: The aim of this study was to examine the osteoarthritis (OA)-related structural changes associated with histological synovitis in end-stage knee OA patients. Methods: Forty end-stage knee OA patients (female: 88%, mean age: 71.8 y) were enrolled. All participants underwent 3.0-T MRI. The structural changes, such as cartilage morphology, subchondral bone marrow lesion (BML), subchondral bone cyst (SBC), subchondral bone attrition (SBA), osteophytes, meniscal lesion and synovitis, were scored using the whole-organ MRI scoring (WORMS) method. Synovial samples were obtained from five regions of interest (ROIs) of the knee joint during total joint replacement surgery. The associations between the histological synovitis score (HSS) and WORMS or the synovial expression levels of cyclooxygenase (COX)-2, interleukin (IL)-1β, IL-6 and transforming growth factor (TGF)–β were examined using Spearman's correlation coefficient. Results: Among the seven OA-related structural changes, the BML, SBC, SBA and synovitis were significantly associated with the HSS ( r = 0.33, 0.35, 0.48 and 0.36, respectively), while other morphological changes were not. Although synovial COX-2, IL-1β or IL-6 expression levels were not associated with the HSS, the synovial TGF-β expression levels were associated with the HSS. Conclusion: The presence of BML, SBC and SBA was associated with histological synovitis in end-stage knee OA patients.